1988
DOI: 10.1002/clc.4960111203
|View full text |Cite
|
Sign up to set email alerts
|

A system approach to intravenous thrombolysis in acute myocardial infarction in community hospitals: The influence of paramedics

Abstract: Summary: During a 3-year period, intravenous streptokinase (IV STK) was given to 110 consecutive patients ages 34-78 in the course of acute myocardial infarction (AMI) in three community hospitals served by the same paramedic system. 1.5 million units of IV STK was given over 30 minutes. Half of the patients were brought to the hospital by paramedics. The average time from onset of pain to administration of IV STK was 107 minutes in the paramedic group and 182 minutes for the others. Of 110 patients, 98 (89%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In the event of AMI symptoms, contacting the EMS may improve survival in the long term because properly trained ambulance personnel can record ECGs, detect and treat life‐threatening complications, such as cardiac arrest, at the accident scene and during transport. In addition, previous research 17–19 reported that patients using ambulance had shorter ‘door‐to‐needle’ times than those using private transportation to arrive at the hospital. Prehospital thrombolysis delivered by ambulance crews may be the most feasible means of achieving timely cardiac reperfusion under some conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the event of AMI symptoms, contacting the EMS may improve survival in the long term because properly trained ambulance personnel can record ECGs, detect and treat life‐threatening complications, such as cardiac arrest, at the accident scene and during transport. In addition, previous research 17–19 reported that patients using ambulance had shorter ‘door‐to‐needle’ times than those using private transportation to arrive at the hospital. Prehospital thrombolysis delivered by ambulance crews may be the most feasible means of achieving timely cardiac reperfusion under some conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the results of previous studies, 7,10–12 we have noted that one of the main reasons cited by patients with AMI for not using an ambulance was quickness of private transport (PT) 13 . Several studies have attempted to substantiate this common perception 5,14–19 . Advocates of EMS consider care to begin when ambulance crews reach the accident scene.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in most centers there is a substantial delay from presentation to actual drug infusion (door-to-needle time). The average door-to-needle time has been reported as 45-90 minutes [4][5][6][7][8][9][10]. Analysis of factors leading to delays in initiating therapy have suggested that a substantial portion of the total delay occurs after patients arrive at the hospital.…”
mentioning
confidence: 99%